Graphene-based, ultrafast Er-doped fiber laser with linearly polarized output pulses - Sobon, Grzegorz; Sotor, Jaroslaw; Pasternak, Iwona; Strupinski, Wlodek; Abramski, Krzysztof (Photonics Letters of Poland, 2014)
We demonstrate an all-fiber, Er-doped fiber laser mode-locked with a graphene-based saturable absorber. The resonator is designed using only polarization maintaining fibers and components, which allows to achieve linearly polarized output beam. The laser delivers 595 fs long pulses at 1560 nm center wavelength with 6.3 nm bandwidth and 67 MHz repetition rate. As a saturable absorber, a graphene-polymer composite was used. Full Text: PDF References Q. L. Bao, H. Zhang, Y. Wang, Z. H. Ni, Z. X. Shen, K. P. Loh, D. Y. Tang, "Atomic-Layer Graphene as a Saturable Absorber for Ultrafast Pulsed Lasers", Adv. Funct. Mater. 19, 3077 (2009). CrossRef T. Hasan, Z. Sun, F. Wang, F. Bonaccorso, P. H. Tan, A. G. Rozhin, A.C. Ferrari, "Nanotube?Polymer Composites for Ultrafast Photonics", Adv. Mater. 21, 3874 (2009). CrossRef H. Zhang, D. Y. Tang, L. M. Zhao, Q. L. Bao, and K. P. Loh, "Large energy mode locking of an erbium-doped fiber laser with atomic layer graphene", Opt. Express 17, 17630 (2009). CrossRef Z. Sun, T. Hasan, F. Torrisi, D. Popa, G. Privitera, F. Wang, F. Bonaccorso, D. M. Basko, A. C. Ferrari, "Graphene Mode-Locked Ultrafast Laser", ACS Nano 4, 803 (2010). CrossRef Z. Sun, D. Popa, T. Hasan, F. Torrisi, F. Wang, E. JR Kelleher, J. C Travers, V. Nicolosi, A. C Ferrari, "A stable, wideband tunable, near transform-limited, graphene-mode-locked, ultrafast laser", Nano Res. 3, 653 (2010). CrossRef D. Popa, Z. Sun, F. Torrisi, T. Hasan, F. Wang, and A. C. Ferrari, "Sub 200 fs pulse generation from a graphene mode-locked fiber laser", Appl. Phys. Lett. 97, 203106 (2010). CrossRef H. Zhang, D. Y. Tang, L. M. Zhao, Q. L. Bao, K. P. Loh, B. Lin, and S. C. Tjin, "Compact graphene mode-locked wavelength-tunable erbium-doped fiber lasers: from all anomalous dispersion to all normal dispersion", Laser Phys. Lett. 7, 591 (2010). CrossRef H. Zhang, Q. Bao, D. Tang, L. Zhao, and K. Loh, "Large energy soliton erbium-doped fiber laser with a graphene-polymer composite mode locker", Appl. Phys. Lett. 95, 141103 (2009). CrossRef J. Xu, S. Wu, H. Li, J. Liu, R. Sun, F. Tan, Q.-H. Yang, P. Wang, "Dissipative soliton generation from a graphene oxide mode-locked Er-doped fiber laser", Opt. Express 20, 23653 (2012). CrossRef P.L. Huang, S. Lin, C. Yeh, H. Kuo, S. Huang, G. Lin, L. Li, C. Su, W. Cheng, "Stable mode-locked fiber laser based on CVD fabricated graphene saturable absorber", Opt. Express 20, 2460 (2012) CrossRef X.H. Li, Y.G. Wang, Y.S. Wang, Y.Z. Zhang, K. Wu, P.P. Shum, X. Yu, Y. Zhang, Q.J. Wang, "All-normal-dispersion passively mode-locked Yb-doped fiber ring laser based on a graphene oxide saturable absorber", Laser Phys Lett. 10, 075108 (2013). CrossRef M. Zhang, E. J. R. Kelleher, F. Torrisi, Z. Sun, T. Hasan, D. Popa, F. Wang, A. C. Ferrari, S. V. Popov, and J. R. Taylor, "Tm-doped fiber laser mode-locked by graphene-polymer composite" Opt. Express 20, 25077 (2012). CrossRef Q. Wang, T. Chen, B. Zhang, M. Li, Y. Lu, and K. P. Chen, "All-fiber passively mode-locked thulium-doped fiber ring laser using optically deposited graphene saturable absorbers", Appl. Phys. Lett. 102, 131117 (2013). CrossRef G. Sobon, J. Sotor, I. Pasternak, A. Krajewska, W. Strupinski, K. M. Abramski, "Thulium-doped all-fiber laser mode-locked by CVD-graphene/PMMA saturable absorber", Opt. Express 21, 12797 (2013). CrossRef G. Sobon, J. Sotor, I. Pasternak, K. Grodecki, P. Paletko, W. Strupinski, Z. Jankiewicz, K.M. Abramski, "Er-Doped Fiber Laser Mode-Locked by CVD-Graphene Saturable Absorber", J. Lightwave Technol. 30, 2770 (2012). CrossRef A. Martinez, K. Fuse, B. Xu, and S. Yamashita, "Optical deposition of graphene and carbon nanotubes in a fiber ferrule for passive mode-locked lasing", Opt. Express 18, 23054 (2010). CrossRef Y. M. Chang, H. Kim, J. H. Lee, and Y. Song, "Multilayered graphene efficiently formed by mechanical exfoliation for nonlinear saturable absorbers in fiber mode-locked lasers", Appl. Phys. Lett. 97, 211102 (2010). CrossRef A. Martinez, K. Fuse, and S. Yamashita, "Mechanical exfoliation of graphene for the passive mode-locking of fiber lasers", Appl. Phys. Lett. 99, 121107 (2011). CrossRef G. Sobon, J. Sotor, K. M. Abramski, "All-polarization maintaining femtosecond Er-doped fiber laser mode-locked by graphene saturable absorber", Laser Phys. Lett. 9, 581 (2012). CrossRef J. Sotor, G. Sobon, K. M. Abramski, "Scalar soliton generation in all-polarization-maintaining, graphene mode-locked fiber laser", Opt. Lett. 37, 2166 (2012). CrossRef M. L. Dennis, I. N. Duling III, "Experimental study of sideband generation in femtosecond fiber lasers", IEEE J. Quantum Electron. 30, 1469 (1994) CrossRef